1996
DOI: 10.1016/s0168-1702(96)01390-1
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation between transmissible gastroenteritis coronavirus (TGEV) structural proteins in the in vitro induction of virus-specific antibodies

Abstract: Following infection of haplotype defined NIH-miniswine with virulent transmissible gastroenteritis coronavirus (TGEV), isolated mesenteric lymph node CD4+ T-cells mounted a specific proliferative response against infectious or inactivated purified virus in secondary in vitro stimulation. A specific, dose-dependent response to the three major recombinant viral proteins: spike (S), membrane (M), and nucleoprotein (N), purified by affinity chromatography, was characterized. Induction of in vitro antibody synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 50 publications
1
38
0
Order By: Relevance
“…Coronavirus comprises three major viral structural proteins: spike (S, 180-220 kDa), membrane (M, 27-32 kDa), and nucleocapsid (N, 55-58 kDa) proteins [5,6]. The S protein is a major viral antigen, binds to a cellular receptor for virus attachment to enter target cells and mediates viral attachment to target cells [7][8][9][10][11][12][13]. The M protein is a trans-membrane protein [14] and it is involved in the assembly process of viral nucleocapsid and membrane [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Coronavirus comprises three major viral structural proteins: spike (S, 180-220 kDa), membrane (M, 27-32 kDa), and nucleocapsid (N, 55-58 kDa) proteins [5,6]. The S protein is a major viral antigen, binds to a cellular receptor for virus attachment to enter target cells and mediates viral attachment to target cells [7][8][9][10][11][12][13]. The M protein is a trans-membrane protein [14] and it is involved in the assembly process of viral nucleocapsid and membrane [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…A successful SARS vaccine could be used prophylactically to protect healthcare workers, laboratory personnel and others in high-risk areas. No vaccines are currently licensed for any of the human CoV, but experimental vaccines have been produced for a number of CoVs for use in chickens, cattle, dogs, cats and swine (Anton et al, 1996;Cavanagh, 2003;Olsen et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…A DNA-based vaccine (Yang et al, 2004), a modified Ankara vaccinia virus (Bisht et al, 2004) and a recombinant attenuated parainfluenza virus have been shown to induce neutralizing antibodies and reduce pulmonary SARS-CoV replication. Studies from other animal CoV vaccines have shown that the CoV nucleocapsid (N) protein may represent another antigen candidate for vaccine development (Anton et al, 1996;Olsen, 1993). Although antibodies to CoV N proteins have no virus-neutralizing activity, there is evidence that the protein may provide protection in vivo by induction of cell-mediated immunity, although it has also been suggested to induce eosinophilic infiltrates resulting in immunopathology (Deming et al, 2006;Enjuanes et al, 1995;Stohlman et al, 1995;Wesseling et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The production of these antigenic complexes has been well documented for TGEV (Fig. 5B) (Anton et al, 1996). Similarly, purified complete viruses could in principle be used as vaccines to protect against PEDV by oral immunization.…”
Section: Progress In the Development Of Pedv Vaccinementioning
confidence: 88%